HISTORICAL AND PHILOSOPHICAL REPRESENTATION OF THE MASS-MEDIA IN THE ANCIENT TIMES - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article conducting a study of the relation between the changes of ways of communication and socio-political life of mankind in ancient times